An Enhanced Bimetallic Optical Fiber SPR Biosensor Using Graphene Oxide for the Label-Free and Sensitive Detection of Human IgG - Qiang Xu; Huiting Yin; Mei Cui; Renliang Huang; Rongxin Su (Sensors)
A fiber-reinforced SPR sensor based on silver-nucleated gold-shell bimetallic nanoparticles and graphene oxide was developed and applied to human IgG detection. The refractive index (RI) sensitivity of the Ag@Au/GO fiber SPR sensor is as high as 4715.9 nm/RIU in the RI range of 1.333–1.365. Staphylococcus aureus protein A (SPA) can specifically recognize and bind to the fragment crystallizable (Fc) of the antibody; it facilitates the highly targeted immobilization of the antibody. SPA and rabbit anti-human IgG were immobilized on the surface of the Ag@Au/GO fiber SPR sensor for the detection of different concentrations of human IgG with a sensitivity of 0.53 nm/μg/mL and detection limits of 0.037 μg/mL. This biosensor based on the mixed structure of GO and Ag@Au combined the common advantages of the two materials. Therefore, our study provides a simple platform for biological analysis and has a good application prospect.